Adapting to climate change : an assessment of vulnerability and risks to human security in the Western Mediterranean Basin - Malak, Dania Abdul; McGlade, Katriona; Pascual, Diana; Pla, Eduard (Springer, 2017)
This book examines the water-related impacts of climate change in the UNESCO Intercontinental Biosphere Reserve of the Mediterranean (IBRM) straddling Spain and Morocco. This is the first in-depth publication on a fascinating transboundary case study; while climate change effects are rather homogenous across the IBRM, differing socio-economic contexts, land-use patterns and policy frameworks in Spain and Morocco mean considerable variations in vulnerability and consequences for human security. The authors have produced a novel and integrated vulnerability assessment that combines hydro-ecological, socio-economic and policy analyses. The interdisciplinary approach and insights contained in this volume will appeal both to those interested in the integration of natural and social sciences as well as those working on water and climate change from academic, practical or policy-oriented perspectives.
Keywords: Climatic changes -- Western Mediterranean.; Human beings -- Effect of climate on -- Western Mediterranean.; Acclimatization -- Western Mediterranean.; Climate change mitigation.; Mediterranean Region -- Western Mediterranean.; elektronické knihy; electronic books